2022
DOI: 10.1039/d2sc01367c
|View full text |Cite
|
Sign up to set email alerts
|

Ensemble representation of catalytic interfaces: soloists, orchestras, and everything in-between

Abstract: Catalytic systems are complex and dynamic, exploring vast chemical spaces on multiple timescales. In this perspective, we discuss the dynamic behavior of fluxional, heterogeneous thermal and electrocatalysts and the ensembles...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 108 publications
(146 reference statements)
1
26
0
Order By: Relevance
“…This also demonstrates that meta stable sites can dominate the reactive adlayer even though they are weaker binding at low coverages entirely due to macroscopic configurational entropy and realistic coverage effects. This corroborates the recent and ongoing work of Sautet and Alexandrova and co-workers [30][31][32][33][53][54][55][56][57][58][59][60][61][62][63][64] demonstrating the catalytic potential of fluxional and meta-stable sites. Overall, our results are very sensible given the parameters used and substantiate the appropriateness of the rate expressions established here for multiple site types.…”
Section: Response To Thermal Excitationsupporting
confidence: 91%
“…This also demonstrates that meta stable sites can dominate the reactive adlayer even though they are weaker binding at low coverages entirely due to macroscopic configurational entropy and realistic coverage effects. This corroborates the recent and ongoing work of Sautet and Alexandrova and co-workers [30][31][32][33][53][54][55][56][57][58][59][60][61][62][63][64] demonstrating the catalytic potential of fluxional and meta-stable sites. Overall, our results are very sensible given the parameters used and substantiate the appropriateness of the rate expressions established here for multiple site types.…”
Section: Response To Thermal Excitationsupporting
confidence: 91%
“…Contrarily to the previous case, the GM is constant in the entire potential range: 100% of Pt 5 (O) 2 is in Pt 5 (O) 2 -I (Figure e), and 96ā€“100% of Pt 5 (OOH) 2 is in Pt 5 (OOH) 2 -I (Figure f). The collapse of the ensemble to a single structure is a signature of particular stability, reached through adsorbate induced geometric change, and making the adsorption stronger . The potential-dependent geometric variation is somewhat more pronounced for Pt 5 (OH) 2 , where the population of GM, Pt 5 (OH) 2 -I, oscillates between 85 and 100% (Figure d).…”
Section: Resultsmentioning
confidence: 98%
“…Using the Curtin-Hammet principle, where the distribution of products is determined by the free energy difference between the two transition states, āˆ†āˆ†G ā€” , we consider the isomer with the lowest transition state energy relative to the global minimum the driver of reactivity for that step. 33,34 To show this for our multi-component systems, we plot barriers on bar charts where all energies are given relative to the global minimum for that composition in Figure 2(b,c). Therefore, accoridng to the Curtin-Hammet principle, the most reactive isomers are the ones with the lowest bar tops in Figure 2(b,c).…”
Section: Resultsmentioning
confidence: 99%
“…32 If a cluster were to have high isomerisation barriers then the ensemble would not thermally equilibrate, and macroscopic properties would be determined by the reduced set of accessible isomers, which could be useful if the prevalent isomers have superior activity. 33 Our most recent work focused on Al 2 O 3 -supported PtGe subnanoclusters, which were pre-pared experimentally after Ge was theoretically predicted to be a suitable dopant. 7 We found that not only were the prepared Pt 4 Ge clusters reasonably stable and selective, but that they slowly converted to a partially-coked form, Pt 4 GeC 2 , which was stable against further coking.…”
Section: Introductionmentioning
confidence: 99%